Successful use of heat as first aid for tropical Australian jellyfish stings. (November 2016) - Little, Mark; Fitzpatrick, Richard; Seymour, Jamie
Abstract: Currently the Australian Resuscitation Council (ARC) recommends dousing with vinegar followed by ice as first aid for jellyfish stings in tropical Australia, with limited evidence to support this recommendation (Li et al., 2013). We report our successful experience in using hot water immersion as first aid in treating two people stung by venomous tropical Australian jellyfish, one by Chironex fleckeri and one by Carukia barnesi . Highlights: Currently recommended first aid for jellyfish stings in tropical Australia is ice. Heat applied to 2 victims stung by Chironex fleckeri and Carukia barnesi . Rapid analgesia was achieved and neither sting victim progressed to exhibit systemic symptoms.